Problem solving in hypertension [electronic resource] - Kennedy, Lee , 1955- (Clinical Pub., 2009)
Suitable for physicians who routinely see patients with hypertension in clinical practice, this book presents a selection of challenging cases seen in everyday practice, highlighting learning points